Condom-vending machines in Italy: a qualitative exploration of gender differences to improve promotion and use. (1st November 2020) - Ramos-Ortiz, Jaziel; Strube, Olivia L.; Kinman, Nicole; Meier, Stephanie; DeMaria, Andrea L.
Abstract: Objectives: The purposes of this study were to explore gender differences in condom purchasing from condom-vending machines (CVMs) and identify ways to improve CVM promotion. Methods: Semi-structured interviews with 42 men and women aged 18–50 years (mean ± standard deviation, 29.1 ± 7.9) and living in or near Florence, Italy, were conducted between May and June 2019. Techniques from expanded grounded theory-guided data analysis allowed for a constant comparative approach to contextualise data and identify emergent themes. Results: Three themes emerged: (1) attitudes and barriers towards CVMs; (2) gender-specific purchasing influences and behaviours; and (3) CVM improvement and promotion. Women and men described varied concerns surrounding CVM purchasing, illuminating reasons for hesitancy. Focussing on CVM quality and improving product offerings were suggested by participants to increase use. Conclusion: Findings offer practical recommendations to guide CVM messaging to increase access to and use of condoms and other personal care items. Men were cited as primary CVM users, expressing practical concerns surrounding CVMs, while, for women, CVM visibility was as much an advantage as a drawback. Reflecting consumer needs via diversified product offerings should be considered a priority for increased CVM use. Working to promote CVMs requires clear messaging that attends to gender norm limitations, details product safety and establishes CVMs as a reliable condom purchase outlet.